Absolute oral bioavailability and pharmacokinetics of canagliflozin: A microdose study in healthy participants. Issue 4 (11th December 2014) - Devineni, Damayanthi; Murphy, Joseph; Wang, Shean‐Sheng; Stieltjes, Hans; Rothenberg, Paul; Scheers, Ellen; Mamidi, Rao N.V.S.
Abstract Absolute oral bioavailability of canagliflozin was assessed by simultaneous oral administration with intravenous [14C]‐canagliflozin microdose infusion in nine healthy men. Pharmacokinetics of canagliflozin, [14C]‐canagliflozin, and total radioactivity, and safety and tolerability were assessed at prespecified timepoints. On day 1, single‐dose oral canagliflozin (300 mg) followed 105 minutes later by intravenous [14C]‐canagliflozin (10 µg, 200 nCi) was administered. After oral administration, the mean (SD) Cmax of canagliflozin was 2504 (482) ng/mL at 1.5 hours, AUC∞ 17, 375 (3555) ng.h/mL, and t1/2 11.6 (0.70) hours. After intravenous administration, the mean (SD) Cmax of unchanged [14C]‐canagliflozin was 17, 605 (6901) ng/mL, AUC∞ 27, 100 (10, 778) ng.h/mL, Vdss 83.5 (29.2) L, Vdz 119 (41.6) L, and CL 12.2 (3.79) L/h. Unchanged [14C]‐canagliflozin and metabolites accounted for about 57% and 43% of the plasma total [14C] radioactivity AUC∞, respectively. For total [14C] radioactivity, the mean (SD) Cmax was 15, 981 (2721) ng‐eq/mL, and AUC∞ 53, 755 (15, 587) ng‐eq.h/mL. Renal (34.5% in urine) and biliary (34.1% in feces) excretions were the major elimination pathways for total [14C] radioactivity. The absolute oral bioavailability of canagliflozin was 65% (90% confidence interval: 55.41; 76.07). Overall, oral canagliflozin 300 mg coadministered with intravenous [14C]‐canagliflozin (10 µg) was generally well‐tolerated in healthy men, with no treatment‐emergent adverse events.